INSIGHTS INTO EXPANSION: A SWOT ANALYSIS & NEED ASSESSMENT OF TAPIOCA MICRO FOOD PROCESSING INDUSTRIES IN SALEM DISTRICT, TAMIL NADU - Bharathi, Venkatesa Palanichamy Narasimma; Muthuswamy, Kalpana; Natarajan, Balakrishnan; Vasudevan, Balamurugan; Appavu, Suresh; Marimuthu, Rajavel; Rajaram, Dhivya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tapioca is a significant crop in Tamil Nadu, India, with Namakkal, Salem, and Kallakurichi being the top producers, with Salem District contributing 13.36%. Micro processing industries play a pivotal role in the economic advancement of Tamil Nadu, significantly contributing to the generation of employment opportunities, revenue, and general economic growth. While the industry study revealed strengthen like naturally formed clusters, successful marketing efforts, and easy access to financial institutions and new technologies, there are also weaknesses like challenges with raw material availability, declining cultivation rates, and environmental concerns. Opportunities for growth include increasing sago consumption, developing value-added products, effective branding strategies, and exploring potential by-products. Threats include competition from new products and imports, high customer expectations, and the use of maize starch as a substitute. Challenges in the industry include the need for harvesting machinery on agricultural farms and processing equipment in sago industries, as well as limited access to institutional finance. Increasing marketing efforts to expand the market for sago and starch products in India, particularly in Tamil Nadu could be beneficial.